Efficacy of platelet-rich plasma in acne scars - Anirudha D Gulanikar; Renu Vidholkar (Wolters Kluwer Medknow Publications, 2019)
Background: Platelet-rich plasma (PRP) is an autologous preparation which contains a large amount of platelets concentrated into a small volume of plasma. PRP provides various growth factors which aid in quick wound healing. It is used as an adjuvant therapy for acne scars. Thus, in this prospective study, the efficacy of PRP as single modality of treatment for acne scars was evaluated. Methods: Thirty patients of Grade 2 and 3 acne scars according to the Goodman and Baron's qualitative acne scar grading system and Fitzpatrick Skin Type IV and V received six sittings of PRP at an interval of 1 month and followed up for 3 months after the completion of six sittings. Patients were assessed for the improvement in the scar grade, 1 month after the last sitting. Pre- and post-treatment comparative photographs and patient's and physician's satisfaction score were used to assess the results. Results: All the types of scars showed response in terms of reduction in size. Rolling scars responded better to PRP as compared to boxcar and ice pick scars. Estimation of improvement with Goodman and Baron's global qualitative acne scarring system showed that out of 30 patients with Grade 2 and 3 acne scars, 50% showed improvement in terms of acne scar grading at the end of the treatment. Among 25 patients with Grade 3 scars, 15 patients (60%) showed improvement by one grade. Adverse effects were mild being limited to transient pain, erythema, edema, and hyperpigmentation. Conclusion: The current study introduces autologous PRP as a cost-effective, well-tolerated office procedure in the treatment of acne scars without serious side effects. Further studies are needed to be carried out to compare the results of this present study.